PEMBIASAAN NILAI-NILAI KEAGAMAAN SEBAGAI KUNCI PEMBENTUKAN KARAKTER RELIGIUS - Mutia Sari; Fajri Ismail; Muhammad Win Afgani (ADIBA : JOURNAL OF EDUCATION, 2023)
This article discusses the importance of character education and religious values in schools. The Ministry of Education and Culture has introduced a structured character education program to instill national character values in the younger generation. Additionally, in facing current moral crises such as free association, violence, crime, and drug abuse, religious education is also crucial. Schools play an important role in shaping the character and religious education of students, using the habituation method to instill Islamic values in students. Schools also have various religious activities to instill religious values in students. This article uses a literature research method with secondary data collection techniques and critical analysis of relevant literature such as books and journals. The results of the analysis are presented descriptively to provide an overview of the formation of character education and the habituation of religious values in schools.